2011
DOI: 10.1124/dmd.111.040105
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Metabolic Pathway of Sipoglitazar, a Novel Antidiabetic Agent: Cytochrome P450-Catalyzed Oxidation of Sipoglitazar Acyl Glucuronide

Abstract: ABSTRACT:Animal pharmacokinetic studies of sipoglitazar, a novel antidiabetic agent, showed that the deethylated metabolite (M-I) and the glucuronide conjugate of sipoglitazar (sipoglitazar-G) appeared to be the key metabolites in the elimination process. M-I was also measured as the main metabolite in the plasma of humans administered sipoglitazar. In vitro metabolic studies were performed to investigate the metabolic pathways from sipoglitazar to M-I in humans. The metabolic profile with human hepatocytes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Sipoglitazar, a novel orally available peroxisome proliferator activated receptor (PPAR) agonist with activities for PPAR α, δ, and γ, was targeted for Type 2 Diabetes Mellitus (T2DM) as a next generation insulin sensitizer. The compound undergoes Phase II biotransformation by conjugation through UDP‐glucuronosyltransferase (UGT) . Following a population pharmacokinetic analysis, UGT2B15 genotype was found to be a covariate for the clearance (CL) of sipoglitazar both in healthy subjects and T2DM patients .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sipoglitazar, a novel orally available peroxisome proliferator activated receptor (PPAR) agonist with activities for PPAR α, δ, and γ, was targeted for Type 2 Diabetes Mellitus (T2DM) as a next generation insulin sensitizer. The compound undergoes Phase II biotransformation by conjugation through UDP‐glucuronosyltransferase (UGT) . Following a population pharmacokinetic analysis, UGT2B15 genotype was found to be a covariate for the clearance (CL) of sipoglitazar both in healthy subjects and T2DM patients .…”
mentioning
confidence: 99%
“…The compound undergoes Phase II biotransformation by conjugation through UDP-glucuronosyltransferase (UGT). 1 Following a population pharmacokinetic analysis, UGT2B15 genotype was found to be a covariate for the clearance (CL) of sipoglitazar both in healthy subjects and T2DM patients. 2 Higher plasma exposure of sipoglitazar was observed in the UGT2B15 Ã 2/ Ã 2 genotype than subjects homozygous for the wild-type allele UGT2B15 Ã 1/ Ã 1 (3.3-fold higher) or heterozygous allele UGT2B15 Ã 1/ Ã 2 (2.2-fold higher).…”
mentioning
confidence: 99%
“… Deethylated sipoglitazar (M1) is detected as the major circulating metabolite following oral administration of sipoglitazar to human subjects. Although M1 appears to be a typical CYP-catalyzed product, investigation into its formation using HLM and human hepatocytes suggests that glucuronidation of sipoglitazar is a prerequisite for the dealkylation step . Phenotyping studies have revealed that sipoglitazar is converted to sipoglitazar-β-1- O -acyl glucuronide (SG1) by UGT2B15 and the formation of deethylated SG1 is exclusively catalyzed by CYP2C8.…”
Section: Glucuronide Conjugates As Substrates Of Cyp2c8mentioning
confidence: 99%
“…Interestingly, sipoglitazar-α-2- O -acyl glucuronide (SG2), which is the acyl migration product of SG1 detected in the bile of rats, is not prone to CYP2C8-catalyzed oxidation. These findings led the authors to speculate that formation of M1 involves the dealkylation of the glucuronide SG1 to deethylated SG1, followed by hydrolysis of the glucuronide intermediate …”
Section: Glucuronide Conjugates As Substrates Of Cyp2c8mentioning
confidence: 99%
“…Sipoglitazar, a novel orally available, peroxisome proliferator–activated receptor (PPAR) agonist with activities for PPAR α, δ, and γ, was targeted for type 2 diabetes mellitus (T2DM). The compound undergoes phase II biotransformation by conjugation catalyzed by UGT . During phase I clinical trials, a bimodal or multimodal distribution of exposure/clearance appeared to be more likely than a normal distribution; this was later evaluated using in vitro data and found to be related to a polymorphism of the UGT2B15 enzyme.…”
mentioning
confidence: 99%